ASSOCIATION BETWEEN PHYSICAL ACTIVITY PRACTICE AND FOOD CONSUMPTION IN SCHOOL TEENAGERS - Lucineia de Pinho; Henrique Nunes Pereira Oliva; Anne Christine Alves Pereira; Ana Clara Veloso Campos de Quadros Godinho; Isaac Brandão Bittencourt Magalhães; Leandro Rodrigues Ramos Rocha; Maria Fernanda Santos Figueiredo Brito; Rosângela Ramos Veloso Silva (Journal of Physical Education)
ABSTRACT Adolescence is a period of transition, marked by habits that can influence the health of individuals in the long run. This study aimed to analyze the association between physical activity and food consumption in adolescents. This is a cross-sectional study with a probabilistic sample of 1.570 school adolescents from Montes Claros, MG, Brazil. The level of physical activity and consumption of fruits, vegetables, sweets, and soda/soft drinks was analyzed. Logistic regression was performed (significance level 5%). Among adolescents, 80.8% were classified as not active and practiced physical activity for at least 60 minutes in less than five days a week. In relation to food, 85.2% and 34.3% of adolescents reported consuming legumes and fruits less than three times a week, respectively. Consumption five times a week or more of treats was 64.1% and soft drinks 90.3%. Those who consumed fruit three times a week or less were 40% more likely to be less active. Those who consumed soda more than five times a week were twice as likely to be little active. Low levels of physical activity were associated with consumption of fruit less than or equal to three times a week and soft drinks greater than five times a week. There is a need to encourage the promotion of healthy lifestyle habits regarding the practice of physical activity and food consumption among adolescents, in school and family contexts.